Investigation of shear strength of interface between roadbase and geosynthetics using large-scale single-stage and multi-stage direct shear test. Issue 6 (17th August 2020) - Xu, Youwei; Williams, David J.; Serati, Mehdi
Abstract : The application of geosynthetics in the road pavement industry as a reinforcement has increased dramatically in recent years. Geosynthetic inclusions can significantly: (i) increase the bearing capacity of the pavement, (ii) prolong the road service life, (iii) reduce maintenance costs, iv) diminish unfavourable large vertical and lateral pavement deformations; and (v) prevent reflective cracking and reduce crack propagation. Although considerable research has been carried out on the interfaces between soils and geosynthetics through large-scale direct shear testing, there is a lack of research in the interfaces between roadbase materials and geosynthetics in pavement engineering. The main innovation of this paper is to investigate the shear strength behaviour of the interfaces existing in a geosynthetic-reinforced pavement. One interface is existing between roadbase and geosynthetic reinforcement for base reinforcement; another one is existing between roadbase and subgrade with geosynthetic reinforcement for subgrade stabilisation. Therefore, a series of laboratory, large-scale direct shear tests was carried out on roadbase materials with and without the inclusion of geosynthetics, under applied normal stresses of 25, 50, 75 or 100 kPa, representing the magnitude of the overburden pressure in the pavement. In addition, theoretical interpretations are developed to back up the experimental results, and to quantify the contribution of different shear strength components mobilised along the interface between roadbase materials and geogrids. Finally, the applicability of multi-stage, large-scale direct shear box testing is assessed by comparing the results obtained with those from conventional single-stage tests obtained in the present experimental study.